Community climate resilience and environmental education: Opportunities and challenges for transformative learning. Issue 7 (3rd July 2022) - Ruiz-Mallén, Isabel; Satorras, Mar; March, Hug; Baró, Francesc
Abstract: Grassroots initiatives towards climate resilience in cities are likely to embed environmental education practices with potential transformative impact among young people. Through interviews and document review, we examine two initiatives involving different non-formal educational actions in Barcelona: a civic ecology practice based on the community gardening of tree pits and an energy citizenship project with the school community. Despite their diverse nature and outcomes, these educational actions promoted by grassroots groups intend to boost young people's critical reflection, responsibility, and agency for taking individual action towards more climate-resilient cities. However, connections between agency, empowerment and transformative learning become more challenging when translated to the collective. Limitations relate to the lack of effective engagement approaches that reinforce social connectedness and local identity, and insufficient evaluation strategies. By discussing these potentials and challenges, we shed light on the synergies concerning transformative learning between the fields of environmental education and urban community resilience.